Polyp number estimation through photogrammetry: a proof of concept using the example of Corallium rubrum - DI FABIO, LUCREZIA; GIORDANO, BRUNA; MOIRAND, LAURINE; BRAMANTI, LORENZO (Mediterranean Marine Science, 2025)
The Mediterranean red coral (Corallium rubrum) is a gonochoric octocoral facing population decline due to overexploitation. Effective management and restocking of this species require accurate estimates of reproductive potential, such as fecundity, which depends on the number of polyps. In the present study, we propose a novel method for estimating the number of polyps in C. rubrum colonies based on polyp density and colony surface. The latter can be determined using existing structure from motion (SfM) techniques. Here, we describe a protocol developed to produce reliable estimates of polyp density, based on counting the number of polyps on branch sections with known surface areas. The mean polyp density, determined on colonies collected in the NW Mediterranean at 25-30 m depth, was 16.9 ± 4.5 polyps cm-2 . Hence, the total number of polyps in a colony can be calculated by multiplying this density with the colony’s total surface area. Method accuracy was assessed by manually counting the exact number of polyps on small-sized colonies and comparing the result to estimates obtained from both our new method and an existing approach based on colony basal diameter. While the latter incurred a mean estimation error of 29%, our new approach yielded a considerably improved accuracy with a mean estimation error of 9%. Further research is needed to validate this new approach across different red coral populations and potentially other coral species.